(3GdcGed aj GdbQGAGJ GdNeSjfs - (3jhSa Hf Ydj Hf MHGQI GdeZQHj GdgPdj, CHh GdbGSe,J (B465 (3g` s ((3Ydj Hf eMeO Hf GdaQZGfj GdeQZjGfj s)
(3ChdgG (B:s
(3fRd GdbQBf Ke bGd aj NHQ BNQ HjfeG CfG CbQC ShQI GdHbQI EP SeYJ s
(3BNQgG (B:s
(3dehGabI GdeUMa eY eGdc GdfGS HGdCda CHh MfjaI Je GdcJGH s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1381s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs